2016
DOI: 10.1111/jdv.13677
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of unsuspected onychomycosis and its causative organisms in a multicentre Canadian sample of 30 000 patients visiting physicians' offices

Abstract: The present data highlights that onychomycosis may be a growing medical concern among ageing patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 25 publications
5
86
0
Order By: Relevance
“…The high prevalence of fungal infections in North America is largely due to the immigration of dermatophytes from other areas of the world such as West Africa and Southeast Asia. The global prevalence of onychomycosis is estimated to be around 5.5%, attributing to 50.0% of all nail disease cases . The risk of onychomycosis increases with age due to poor peripheral circulation, diabetes, repeated nail trauma, longer exposure to pathogenic fungi, suboptimal immune function, inactivity, and/or the inability to maintain good foot care .…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…The high prevalence of fungal infections in North America is largely due to the immigration of dermatophytes from other areas of the world such as West Africa and Southeast Asia. The global prevalence of onychomycosis is estimated to be around 5.5%, attributing to 50.0% of all nail disease cases . The risk of onychomycosis increases with age due to poor peripheral circulation, diabetes, repeated nail trauma, longer exposure to pathogenic fungi, suboptimal immune function, inactivity, and/or the inability to maintain good foot care .…”
Section: Epidemiologymentioning
confidence: 99%
“…The global prevalence of onychomycosis is estimated to be around 5.5%, attributing to 50.0% of all nail disease cases . The risk of onychomycosis increases with age due to poor peripheral circulation, diabetes, repeated nail trauma, longer exposure to pathogenic fungi, suboptimal immune function, inactivity, and/or the inability to maintain good foot care . Toenail onychomycosis is more common in males with Candida fingernail onychomycosis more common in women .…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials usually enroll dermatophyte-confirmed onychomycosis, yet recent epidemiological studies have reported a prevalence of nondermatophyte/mixed infections ranging from 28 to 48% [13,14]. Although the present study included few patients with these infections ( n = 18), mycological cure was observed in 13 patients.…”
Section: Discussionmentioning
confidence: 60%
“…Onychomycosis is a fungal infection of nails [1]. It accounts for half of all nail disorders and its prevalence has been increasing.…”
Section: Introductionmentioning
confidence: 99%